O SENTIDO DE MISSÃO NO IMAGINÁRIO POLÍTICO NORTE-AMERICANO (Revista de História Regional, 2007)
This article examines the concepts and myths associated to one of the most important international attendance programs crated by President Kennedy: The Peace Corps. From this case some matters are raised regarding identity, political and religious traditions and intercultural dialogues.